2014
DOI: 10.3389/fnins.2014.00184
|View full text |Cite
|
Sign up to set email alerts
|

Sexually dimorphic nuclei in the spinal cord control male sexual functions

Abstract: Lower spinal cord injuries frequently cause sexual dysfunction in men, including erectile dysfunction and an ejaculation disorder. This indicates that the important neural centers for male sexual function are located within the lower spinal cord. It is interesting that the lumbar spinal segments contain several neural circuits, showing a clear sexually dimorphism that, in association with neural circuits of the thoracic and sacral spinal cord, are critical in expressing penile reflexes during sexual behavior. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 62 publications
2
30
0
Order By: Relevance
“…The spinal cord of genetically male rats carrying the Tfm allele is hyperfeminine and exhibits even fewer GRP-positive neurons than dose the spinal cord of wild-type females. The spinal cord of Tfm males showed fewer GRP-positive neurons than that of wild-type males, as was expected [2,5]. In addition, GRPexpressing neurons in males express ARs but do not express estrogen receptors [5].…”
Section: Identification Of the Grp System And Its Local Neural Circuisupporting
confidence: 62%
See 3 more Smart Citations
“…The spinal cord of genetically male rats carrying the Tfm allele is hyperfeminine and exhibits even fewer GRP-positive neurons than dose the spinal cord of wild-type females. The spinal cord of Tfm males showed fewer GRP-positive neurons than that of wild-type males, as was expected [2,5]. In addition, GRPexpressing neurons in males express ARs but do not express estrogen receptors [5].…”
Section: Identification Of the Grp System And Its Local Neural Circuisupporting
confidence: 62%
“…In male rats, the spinal nucleus of the bulbocavernosus (SNB) is a cluster of motor neurons located in the fifth and sixth lumbar and first sacral segments of the spinal cord (L5-S1 level) [2,[15][16][17]. These motor neurons and their target muscles, the bulbocavernosus and levator ani, which are attached to the base of the penis, play an important role in male copulatory behavior [15,[17][18][19].…”
Section: Sakamoto and Otimentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 This indicates that important neural control circuits for penile function are located within the lower spinal cord. [3][4][5][6][7][8][9] We previously demonstrated that a population of gastrin-releasing peptide (GRP) neurons in the lumbar spinal cord has an important role in penile erection and ejaculation in rats. 10,11 This system of GRP neurons is sexually dimorphic, being prominent in male rats but vestigial or absent in female rats.…”
Section: Introductionmentioning
confidence: 99%